2016
DOI: 10.1097/ana.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clevidipine on Cerebral Blood Flow Velocity and Carbon Dioxide Reactivity in Human Volunteers

Abstract: Clevidipine infusion did not significantly increase CBFV nor was cerebral CO2 reactivity reduced during maximal-dose clevidipine infusion. Further systematic investigation of clevidipine in patients with central nervous system pathology seems justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This is a shortacting CCB administered as a continuous infusion for rapid control of hypertension. One study has evaluated the cerebrovascular effects of clevidipine and it was not found to significantly increase cerebral blood flow velocity (CBFV) or CO 2 responsiveness [15]. The key to reducing adverse effects from CCB agents is to avoid abrupt changes in dosage and maintaining euvolemia throughout the duration of treatment.…”
Section: Nicardipinementioning
confidence: 99%
“…This is a shortacting CCB administered as a continuous infusion for rapid control of hypertension. One study has evaluated the cerebrovascular effects of clevidipine and it was not found to significantly increase cerebral blood flow velocity (CBFV) or CO 2 responsiveness [15]. The key to reducing adverse effects from CCB agents is to avoid abrupt changes in dosage and maintaining euvolemia throughout the duration of treatment.…”
Section: Nicardipinementioning
confidence: 99%
“…It showed effectiveness and safety for acute HBP control in patients with ICH [10,13,17,18], aIS [7,13,14,15,18], aSAH [13,18] and after neurosurgical procedures [15,16,19], but little evidence exists regarding its effectiveness and safety in perioperative management of HBP after mechanical thrombectomy, embolization of aneurysm causing aSAH, ICH requiring surgical treatment and interventional neuroradiology procedures. Clevidipine has been shown not increase brain blood ow velocity or decrease brain reactivity to C0 2 in healthy human volunteers according to evidence [20], but the real signi cance of this nding is unknown in damaged brain of neurocritical patients.…”
Section: Introductionmentioning
confidence: 98%